Liver Transplant Recipient, Caregiver, and Provider Perceptions of Cardiovascular Disease and Related Risk Factors After Transplant. Issue 5 (30th April 2021) - VanWagner, Lisa B.; Gordon, Elisa; Adamski, Lindsay; Kosirog, Megan; Daud, Amna; Finn, Daniel J.; Lloyd‐Jones, Donald M.; Holl, Jane L.
Abstract : Liver transplant recipients (LTRs) are at high risk for cardiovascular disease (CVD). We sought to characterize LTR, informal caregiver, and health care provider perceptions about CVD care after liver transplantation (LT) to inform the design of solutions to improve care. Participants included adult LTRs, their caregivers, and multispecialty health care providers recruited from an urban tertiary care network who participated in 90‐minute focus groups and completed a brief survey. Focus group transcripts were analyzed using thematic analysis, and survey data were analyzed using descriptive statistics. A total of 17 LTRs, 9 caregivers, and 22 providers participated in 7 separate focus groups. Most (93.3%) LTRs and caregivers were unaware of the risk of CVD after LT. Although 54.5% of providers were confident discussing CVD risk factors with LTRs, only 36.3% were confident managing CVD risk factors in LTRs, and only 13.6% felt that CVD risk factors in their LTR patients were well controlled. Barriers to CVD care for LTRs included (1) lack of awareness of CVD risk after LT, (2) lack of confidence in an ability to provide proper CVD care to LTRs, (3) reluctance to provide CVD care without transplant provider review, and (4) complexity of communication with the multidisciplinary LTR care team about CVD care. Participant recommendations included improved education for LTRs and caregivers about CVD risk factors, electronic health record alerts for providers, clearly defined CVD care provider roles, increased use of the transplant pharmacist, and multidisciplinary provider meetings to discuss care plans for LTRs. Multiple barriers to CVD care after LT were identified, and targeted recommendations were proposed by participants. Transplant centers should integrate participants' recommendations when designing interventions to optimize CVD care for LTRs.